IMPLEMENTASI KEBIJAKAN PROGRAM PEMBINAAN DAN PENGAWASAN IZIN USAHA PERIKANAN TANGKAP DINAS KELAUTAN DAN PERIKANAN PROVINSI RIAU DI KABUPATEN BENGKALIS - Kartika, Maironi; Meiwanda, Geovani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Abstract This study aims to find out and describe how the implementation of fisheries business policies through the program of fostering and supervising capture fisheries business permits from the Maritime Affairs and Fisheries Service of the Riau Province in Bengkalis Regency, knowing the supporting and inhibiting factors and the efforts made by the government to overcome the obstacles that occur. This study uses a qualitative research method where data collection techniques are through observation, interviews and documentation. The theory used is the policy implementation model according to Merrile Grindle in Leo Agustino. The results showed that the implementation of fisheries business policies through the program of fostering and supervising capture fisheries business permits in Bengkalis Regency has not gone well due to the low mindset of fishermen, budget constraints, lack of coordination in program implementation, the presence of individuals or parties who take personal advantage , limitations in the use of fishing gear and fishing areas with the issuance of Riau Province Regional Regulation number 5 of 2017, there is no fish shelter (TPI) available for fishermen and there is competition from local fishermen against fishermen from outside the area. Keywords: implementation, policy, fishery business, program for fostering and supervising capture fisheries.